Retrospective Overview of Medical Tourism and Related Research: A Bibliometric Analysis - Yadav, Prashant Kumar; Tamta, Anil Kumar (ASEAN Journal on Hospitality and Tourism, 2025)
The study presents a comprehensive knowledge mapping and bibliometric analysis of medical tourism research to understand global trends and directions. The exponential growth in medical tourism is driven by factors such as cost savings, access to specialised treatments, and reduced waiting times. The bibliometric analysis of research trends was conducted using CiteSpace 6.3. R1 and VOSviewer 1.6.20 software. The extracted dataset from the Scopus database includes 630 articles. The analysis highlighted significant international collaborations, with the United States, India, and Malaysia as prominent contributors. The publications initially rose in 2021, due to increased research funding and academic interest sparked by the COVID-19 pandemic, followed by a decline, indicating a stabilisation or shift in research priorities. The theoretical implications of this research paper include highlighting the global collaboration and contributions of different countries to medical tourism research, understanding the impact of global events like the COVID-19 pandemic on research trends, and identifying emerging themes and patterns that can guide future studies and policy-making in the field. The findings have substantial practical implications for policymakers, healthcare providers, and researchers.